REFORMASI BIROKRASI DALAM PENATAAN KELEMBAGAAN PEMERINTAHAN DAERAH DI PEMPROV. NTT - Indriyati Indriyati (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2017)
This study examines bureaucratic reforrm in the provincial govermenth through the implementation of regional organizational structuring policies (OPD), in the provincial scope NTT according to PP No. 18 Th 2016. But The actual implementation of this policy is a change from the previous government regulation that is PP N0. 41 Th 2007. There must be some changes in the nomenclature of the regional apparatus organization (OPD) under the rule. But the important thung is that the main purpose of the policy must be realized. Where changes in the nomenclature of the organizational of regional apparatus organizational(OPD), will result in better value of effeciency and institutional effectiveness. This reseaarch is done by qualitative method, and concludes that basically in the implementation of the policy of organizing the regional apparatus of the province NTT, however with suggestions or recommendations of researchers is expexted to have implovement measures made by the government in implementing the next policy and in the implementation of government.